Strategi Manajemen Pengembangan Sarana dan Prasarana dalam Meningkatkan Kualitas Pendidikan Melalui Bantuan Operasional Sekolah - Aprilliantoni; Hilaliyah; Siti Maesaroh (Jurnal Dirosah Islamiyah, 2024)
The purpose of this study is to analyze the strategy and management of educational infrastructure development in improving the quality of education through school operational assistance. This study uses a library research approach. Data analysis through information related to the school operational assistance program from various secondary data sources such as journals, papers, articles, and news from websites (internet), and others. The results of the study indicate that the school operational assistance (BOS) program has proven effective in supporting the strategy and management of educational infrastructure development so that there is an increase in the quality of education in schools.